Leaders in the Classroom: Using Teaching as a Context for Measuring Leader Identity - Nadelson, Louis S.; Booher, Loi; Turley, Michael (Frontiers in Education, 2020)
There is a gap in the comprehensive understanding of the teacher leader identity due to a lack of research on teachers’ perceptions of being leaders in the context of classroom teaching. To address the gap we examined teachers expression of leader identity attributes in the context of classroom teaching. The responses of the 91 K-12 teachers who participated in our exploratory study, revealed variations in levels of leader identity attributes based on individual differences. Most participants tended to perceive teachers’ primary role as a conveyer of knowledge, and yet strongly agreed that teachers are role models. We exposed a disconnect between perceptions of leading between why the participants became teachers and their perceptions of the role of a teacher. Thus, while teachers express attributes of a leader identity, they tend to not perceive leading as a primary role in teaching, indicating teacher leader identity is likely contextual rather than professional.